Studi Tafsir Tematik Peluang Independent Woman Sebagai Instrumen Stabilitas Ekonomi Keluarga di Kelurahan Kenangan Baru Perspektif Al-Misbah - Yasmin, Athiyah; Munandar, Munandar (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
This study aims to examine the opportunities for independent women as an instrument of family economic stability from the perspective of the thematic interpretation of Al-Misbah, focusing on the economic role of working women in the Belibis IV Neighborhood, Kenangan Baru Village, Deli Serdang. The approach used is descriptive qualitative with case study and thematic interpretation methods. Data were collected through library research on the interpretation of Al-Misbah by M. Quraish Shihab and in-depth interviews with four working women informants from various professional backgrounds. The results of the study identified that women have a real contribution to the main family income, increasing household welfare, and influence on domestic decision-making. The main themes that emerged from the field data include the dual role of women, the psychosocial impact of financial independence, and the theological legitimacy of women's work based on the interpretation of QS. An-Nisa [4]: 32. The interpretation of Al-Misbah provides a contextual meaning that emphasizes the fair distribution of gifts and recognition of the efforts of each individual, both men and women. This study has implications for strengthening the discourse of gender interpretation in contemporary Islam and encouraging policies that support equality of family-based economic roles. Further studies are needed to encompass broader regional and professional contexts to enrich understanding of the dynamics of women's economic roles in Muslim societies.